Accurate deuterium spectroscopy for fundamental studies. (July 2018) - Wcisło, P.; Thibault, F.; Zaborowski, M.; Wójtewicz, S.; Cygan, A.; Kowzan, G.; Masłowski, P.; Komasa, J.; Puchalski, M.; Pachucki, K.; Ciuryło, R.; Lisak, D.
Highlights: Weak quadrupole S(2) 2-0 line in self-perturbed D2 is measured. Collisional line-shape effects and energy of this rovibrational transition are calculated. The velocity-changing collisions are handled with the hard-sphere collisional kernel. The experimental and theoretical pressure broadening and shift are consistent within 5. We observe 3.4 sigma discrepancy between experimental and theoretical line position. Abstract: We present an accurate measurement of the weak quadrupole S(2) 2-0 line in self-perturbed D2 and theoretical ab initio calculations of both collisional line-shape effects and energy of this rovibrational transition. The spectra were collected at the 247–984 Torr pressure range with a frequency-stabilized cavity ring-down spectrometer linked to an optical frequency comb (OFC) referenced to a primary time standard. Our line-shape modeling employed quantum calculations of molecular scattering (the pressure broadening and shift and their speed dependencies were calculated, while the complex frequency of optical velocity-changing collisions was fitted to experimental spectra). The velocity-changing collisions are handled with the hard-sphere collisional kernel. The experimental and theoretical pressure broadening and shift are consistent within 5% and 27%, respectively (the discrepancy for shift is 8% when referred not to the speed averaged value, which is close to zero, but to the range of variability of the speed-dependent shift). We use our high pressure measurement to determine the energy, ν 0, of the S(2) 2-0 transition. The ab initio line-shape calculations allowed us to mitigate the expected collisional systematics reaching the 410 kHz accuracy of ν 0 . We report theoretical determination of ν 0 taking into account relativistic and QED corrections up to α 5 . Our estimation of the accuracy of the theoretical ν 0 is 1.3 MHz. We observe 3.4 σ discrepancy between experimental and theoretical ν 0 .